Sodium-ion battery electrolyte additive and composition thereof, electrolyte and sodium-ion battery containing electrolyte
By using fluorine-containing cyclic sulfates and other fluorine-containing carbonates as electrolyte additives in sodium ion batteries, the problem of high impedance in the electrolyte solution is solved, and the battery's low internal resistance and high discharge start is achieved Capacity and excellent cycling performance improve the overall performance and oxidation resistance of the battery.
Patent Information
- Application Number
- CN202411276810.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-12
- Publication Date
- 2024-12-24
Smart Images

Figure CN119181853A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of secondary batteries, and in particular to a sodium ion battery electrolyte additive and a composition thereof, an electrolyte and a sodium ion battery containing the electrolyte. Background Art
[0002] Compared with lithium-ion batteries, sodium-ion batteries exhibit a series of significant advantages, including more stable raw material supply, relatively low production cost, excellent fast charging and discharging potential, superior performance in low temperature environments and no risk of over-discharge. These characteristics make it have broad application prospects in many fields such as low-energy density electric passenger vehicles, two-wheeled electric vehicle market, energy storage systems and power tools.
[0003] At the same time, the research on electrolyte modification of sodium ion batteries is also a key link. The research focuses on introducing new film-forming additives that can form a uniform and dense solid electrolyte interface film (SEI film) inside the battery. This protective film is crucial to ensure the stability of the battery during the charging and discharging process. It can effectively prevent the continuous decomposition of the electrolyte and the occurrence of harmful side reactions, thereby significantly improving the cycle stability and overall performance of the battery.
[0004] However, although the new film-forming additives introduced by the modification research of the electrolyte can improve the composition of the CEI / SEI film, the CEI / SEI film formed often has a large impedance, which leads to an increase in the DC internal resistance of the battery and deterioration of high and low temperature performance. Therefore, in order to make the sodium ion battery have low internal resistance, high initial discharge capacity and excellent cycle performance, it is particularly important to develop electrolyte additives suitable for the sodium ion battery system. Summary of the invention
[0005] In order to make a sodium ion battery have low internal resistance, high initial discharge capacity and excellent cycle performance, the present application provides a sodium ion battery electrolyte additive and a composition thereof, an electrolyte and a sodium ion battery containing the electrolyte.
[0006] In a first aspect, the present application provides an electrolyte additive for a sodium ion battery, wherein the additive is a fluorinated cyclic sulfate compound, wherein the fluorinated cyclic sulfate has a structure as described in formula (I):
[0007]
[0008] Formula (I), wherein R is selected from an alkylene group having 2 to 6 carbon atoms, including a halogen-substituted alkylene group, a hydrocarbonoxy-substituted alkylene group, an alkenyl-substituted alkylene group, an alkynyl-substituted alkylene group, an alkylene group substituted with a benzene ring or a halogenated benzene ring, and x is 1, 2, or 3.
[0009] Furthermore, the fluorine-containing cyclic sulfate having the structure shown in formula (I) is one of the following compounds:
[0010]
[0011] Furthermore, the content of the fluorine-containing cyclic sulfate is 0.1-5% of the total mass of the non-aqueous electrolyte.
[0012] In a second aspect, the present application provides a sodium ion battery electrolyte additive composition, which comprises the fluorine-containing cyclic sulfate esters as described in claim 1 and other additives.
[0013] Furthermore, the other additives are selected from fluorine-containing carbonates, including at least one of fluorine-containing cyclic carbonates and fluorine-containing linear carbonates, and the amount of the other additives is 0.5-5% of the total mass of the non-aqueous electrolyte.
[0014] Further, the other additives are selected from at least one of fluoroethylene carbonate (FEC), difluoroethylene carbonate (DFEC), trifluoromethylethylene carbonate (TFPC), 2,2,2-trifluoroethoxymethylethylene carbonate, hexafluoroisopropoxymethylethylene carbonate, 2,2,3,3,3-pentafluoropropoxymethylethylene carbonate, bis(trifluoromethyl)carbonate (DTFMC), bis(pentafluoroethyl)carbonate, bis(2,2,2-trifluoroethyl)carbonate, bis(2,2,3,3-tetrafluoropropyl)carbonate, methyl-2,2,2-trifluoroethylcarbonate (FEMC), ethyl-2,2,2-trifluoroethylcarbonate, (2,2,3,3,3-pentafluoropropyl)-methyl carbonate (PFPMC), and bis(fluoromethyl)carbonate.
[0015] In a third aspect, the present application provides a sodium ion battery electrolyte, which adopts the following technical solution: a sodium ion battery electrolyte, comprising an electrolyte, a non-aqueous solvent and an additive, characterized in that the additive comprises any one of the additives of claims 1 to 6 and a combination thereof.
[0016] Furthermore, the sodium salt electrolyte is at least one of sodium hexafluorophosphate, sodium difluorophosphate, sodium bis(oxalatoborate), sodium difluorooxalatoborate, sodium bis(fluorosulfonyl imide), sodium bis(trifluoromethylsulfonyl imide), sodium trifluoromethylsulfonate, sodium perchlorate, and sodium tetrafluoroborate, and the molar concentration of the sodium salt electrolyte in the non-aqueous electrolyte is 0.8 to 1.5 mol / L.
[0017] Furthermore, the non-aqueous organic solvent is at least one of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, dipropyl carbonate, ethylene carbonate, methyl propyl carbonate, methyl butyl carbonate, propylene carbonate, γ-butyrolactone, methyl acetate, ethyl acetate, propyl acetate, butyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,2-dimethoxypropane, 2,2-dimethoxypropane, ethylene glycol dimethyl ether, tetrahydrofuran, and 2-methyltetrahydrofuran.
[0018] In a fourth aspect, the present application provides a sodium ion battery, which adopts the following technical solution: a sodium ion battery, characterized in that it comprises a positive electrode material, a negative electrode material and the non-aqueous electrolyte described in any one of claims 7 to 9.
[0019] Furthermore, the positive electrode material is selected from at least one of polyanion positive electrode materials, layered oxide positive electrode materials, and Prussian blue (Prussian white) positive electrode materials; the negative electrode material includes but is not limited to at least one of soft carbon, hard carbon, sodium titanate, and a metal that can form an alloy with sodium.
[0020] The present invention has the following beneficial effects:
[0021] The present invention adds fluorine-containing cyclic sulfate as an additive to a non-aqueous electrolyte. Since the fluorine-containing additive has a lower HOMO energy level, the oxidation resistance of the non-aqueous electrolyte can be improved and the electrochemical window of the non-aqueous electrolyte can be widened. At the same time, the cyclic sulfate can participate in the formation of the negative electrode SEI film, which can stabilize the electrode interface and significantly reduce the impedance of the negative electrode surface, thereby reducing the overall impedance of the battery and improving the battery's rate performance, high temperature performance, cycle life, etc. DETAILED DESCRIPTION
[0022] The technical solution of the present invention is exemplarily described below through specific embodiments. The specific embodiments described here are only for explaining the present invention and are not intended to limit the present invention.
[0023] [Example 1]
[0024] (1) Preparation of non-aqueous electrolyte
[0025] In a clean glove box filled with nitrogen with water and oxygen content ≤ 0.1ppm, ethylene carbonate (EC), propylene carbonate (PC), and diethyl carbonate (DEC) were mixed in a volume ratio of 1:1:2. Sodium hexafluorophosphate was added to the prepared non-aqueous solvent, mixed and dissolved thoroughly, and a basic electrolyte containing 1 mol / L sodium hexafluorophosphate was prepared.
[0026] Add trifluoromethyl vinyl sulfate having a structure shown in formula (I-1) to the basic electrolyte prepared above, wherein the mass content of trifluoromethyl vinyl sulfate of formula (I-1) is 1% based on 100% of the total mass of the electrolyte.
[0027] (2) Fabrication of sodium ion batteries
[0028] The positive electrode active material sodium iron phosphate pyrophosphate (Na4Fe3(PO4)2P2O7), conductive carbon black, and binder polyvinylidene fluoride (PVDF) are added and dispersed in N-methyl-2-pyrrolidone (NMP) in a mass ratio of 96:2:2, and are fully mixed to obtain a positive electrode slurry; the positive electrode slurry is coated on both sides of a carbon-coated aluminum foil, and after drying, rolling, and cutting, a positive electrode sheet is obtained for standby use.
[0029] The negative electrode active material hard carbon, conductive carbon black, binder sodium carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR) are added and dispersed in distilled water in a mass ratio of 96:1:1.5:1.5, and mixed thoroughly to obtain a negative electrode slurry; the negative electrode slurry is coated on both sides of a double-sided smooth aluminum foil, and after drying, rolling and cutting, a negative electrode sheet is obtained for standby use.
[0030] The positive electrode sheet, polypropylene porous isolation membrane, and negative electrode sheet were stacked to prepare an electrode assembly, and the pole ears were welded on the positive and negative electrodes respectively using an ultrasonic spot welder. The electrode assembly was then placed in an aluminum foil bag and vacuum dried at 80°C for 48 hours to obtain a dry battery cell.
[0031] In a glove box filled with nitrogen or argon with a water and oxygen content of ≤0.1ppm, the prepared non-aqueous electrolyte is injected into the fully dried battery cell. After the injection, the battery cell is sealed and allowed to stand, formed, aged, sealed again, and divided to obtain the sodium ion battery used in Example 1.
[0032] The electrochemical performance of the non-aqueous electrolyte and the sodium ion battery was tested, and the results are shown in Table 2.
[0033] [Example 2-11]
[0034] The non-aqueous electrolyte was prepared and the sodium ion battery was manufactured according to the method steps of Example 1, the only difference being the material structure and amount of the additive in the non-aqueous electrolyte, as shown in Table 1.
[0035] The electrochemical performance of the non-aqueous electrolyte and the sodium ion battery was tested, and the results are shown in Table 2.
[0036] [Comparative Example 1]
[0037] (1) Preparation of non-aqueous electrolyte
[0038] In a clean glove box filled with nitrogen with water and oxygen content ≤ 0.1ppm, ethylene carbonate (EC), propylene carbonate (PC), and diethyl carbonate (DEC) were mixed in a volume ratio of 1:1:2. Sodium hexafluorophosphate was added to the prepared non-aqueous solvent, mixed and dissolved thoroughly, and a basic electrolyte containing 1 mol / L sodium hexafluorophosphate was prepared.
[0039] Fluoroethylene carbonate (FEC) was added to the basic electrolyte prepared above, wherein the mass content of fluoroethylene carbonate (FEC) was 2% based on 100% of the total mass of the electrolyte.
[0040] (2) Fabrication of sodium ion batteries
[0041] The positive electrode active material sodium iron phosphate pyrophosphate (Na4Fe3(PO4)2P2O7), conductive carbon black, and binder polyvinylidene fluoride (PVDF) are added and dispersed in N-methyl-2-pyrrolidone (NMP) in a mass ratio of 96:2:2, and are fully mixed to obtain a positive electrode slurry; the positive electrode slurry is coated on both sides of a carbon-coated aluminum foil, and after drying, rolling, and cutting, a positive electrode sheet is obtained for standby use.
[0042] The negative electrode active material hard carbon, conductive carbon black, binder sodium carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR) are added and dispersed in distilled water in a mass ratio of 96:1:1.5:1.5, and mixed thoroughly to obtain a negative electrode slurry; the negative electrode slurry is coated on both sides of a double-sided smooth aluminum foil, and after drying, rolling and cutting, a negative electrode sheet is obtained for standby use.
[0043] The positive electrode sheet, polypropylene porous isolation membrane, and negative electrode sheet were stacked to prepare an electrode assembly, and the pole ears were welded on the positive and negative electrodes respectively using an ultrasonic spot welder. The electrode assembly was then placed in an aluminum foil bag and vacuum dried at 80°C for 48 hours to obtain a dry battery cell.
[0044] In a glove box filled with nitrogen or argon with water and oxygen content ≤0.1ppm, the prepared non-aqueous electrolyte is injected into the fully dried battery cell. After the injection, the battery cell is sealed and allowed to stand, formed, aged, sealed again, and divided to obtain the sodium ion battery used in Comparative Example 1.
[0045] The electrochemical performance of the non-aqueous electrolyte and the sodium ion battery was tested, and the results are shown in Table 2.
[0046] [Comparative Example 2]
[0047] The non-aqueous electrolyte was prepared and the sodium ion battery was manufactured according to the method steps of Comparative Example 1, the only difference being the material structure and amount of the additive in the non-aqueous electrolyte, as shown in Table 1.
[0048] The electrochemical performance of the non-aqueous electrolyte and the sodium ion battery was tested, and the results are shown in Table 2.
[0049] Table 1 Additive components and dosages in non-aqueous electrolytes of Examples 1 to 11 and Comparative Examples 1 to 2
[0050]
[0051]
[0052] The performance testing methods of the non-aqueous electrolyte and sodium ion battery involved in this application are as follows:
[0053] (1) First capacity and first efficiency test of sodium ion battery: At 25°C, charge the battery to 3.0V at 0.1C constant current, at which time the charge amount is Q1, then charge it to 3.2V at 0.2C constant current, at which time the charge amount is Q2, then let it stand for 4 hours and seal the battery twice. After the second seal, charge it to 4.0V at 0.5C constant current, then charge it to a cut-off current of 0.05C at constant voltage. At this time, the charge amount is Q3. Then discharge the battery to 1.5V at 0.5C constant current, at which time the discharge amount is Q. The first capacity of the battery is Q, and the first efficiency = Q / (Q1+Q2+Q3)×100%.
[0054] (2) DC internal resistance (DCR) test: At 25°C, charge the battery to 4V with constant current and constant voltage, with a cut-off current of 0.05C, and then discharge the battery to 1.5V with a constant current of 0.5C. The discharge capacity is Q1. Charge the battery to 4V with constant current and constant voltage again, with a cut-off current of 0.05C. Then discharge the battery with a constant current of 0.5C to a capacity of Q1 / 2, let it stand for 1h, record the voltage as V1, discharge the battery with a constant current of 3C for 10s, and record the voltage at this time as V2. DC internal resistance DCR = (V1-V2) / 3C.
[0055] (3) Normal temperature cycle test: At 25°C, charge the battery to 4V at 1C constant current, then let it stand for 10 minutes, then discharge it to 1.5V at 1C constant current, let it stand for 10 minutes. This is a cycle, and the discharge capacity at this time is recorded as Q1. The battery is allowed to continue the above cycle, and the discharge capacity of the nth cycle is recorded as Q n , capacity retention rate = Q n / Q1×100%
[0056] (4) High temperature storage test: At 25°C, charge the battery to 4V at 0.5C constant current and constant voltage, with a cut-off current of 0.05C, and then discharge it to 1.5V at 0.5C constant current, and record the discharge amount Q1 at this time. Then charge the battery to 4V at 0.5C constant current and constant voltage, with a cut-off current of 0.05C, measure the battery thickness as D0, and then put the battery into a 60°C oven and store it for 7×24h. Then take it out and discharge it to 1.5V at 0.5C constant current at 25°C. Record the discharge amount as Q2. And measure the battery thickness as D1. Then charge the battery to 4V at 0.5C constant current and constant voltage again, with a cut-off current of 0.05C, and then discharge it to 1.5V at 0.5C constant current, and record the discharge amount at this time as Q3. Battery thickness expansion rate = (D1-D0) × 100%; capacity retention rate = (Q2 / Q1) × 100%; capacity recovery rate = (Q3 / Q1) × 100%.
[0057] Table 2 Test results of non-aqueous electrolyte and sodium ion battery performance in Examples 1 to 11 and Comparative Examples 1 to 2
[0058]
[0059] The addition of a single additive fluorinated cyclic sulfate ester I-1, I-2, I-3 is compared with the addition of other single additives, and Examples 1-3 and Comparative Example 1-2 are compared. The room temperature (25°C) 1C cycle effect of a single fluorinated cyclic sulfate ester additive is better than that of other additives. This is because the fluorinated additive has a lower HOMO energy level, which can improve the oxidation resistance of the non-aqueous electrolyte, and the cyclic sulfate ester can react to form a film on the electrode surface, protect the electrode, and increase its cycle life. The single additive fluorinated cyclic sulfate ester I-1, I-2, I-3 is compounded with other additives and compared, and Examples 1-3 and Examples 4-11 are compared. Compounding it with other additives can further improve its cycle life, and effectively reduce the capacity retention rate after high-temperature storage and reduce battery expansion.
Claims
1. A sodium ion battery electrolyte additive, characterized in that: It is a fluorinated cyclic sulfate compound having the structure described in formula (I): Formula (I), wherein R is selected from an alkylene group having 2 to 6 carbon atoms, including a halogen-substituted alkylene group, a hydrocarbonoxy-substituted alkylene group, an alkenyl-substituted alkylene group, an alkynyl-substituted alkylene group, an alkylene group substituted with a benzene ring or a halogenated benzene ring, and x is 1, 2, or 3.
2. A sodium ion battery electrolyte additive according to claim 1, characterized in that: The fluorine-containing cyclic sulfate having the structure shown in formula (I) is one of the following compounds:
3. The sodium ion battery electrolyte additive according to claim 2, characterized in that: The content of the fluorine-containing cyclic sulfate is 0.1-5% of the total mass of the non-aqueous electrolyte.
4. A sodium ion battery electrolyte additive composition, characterized in that: The additive composition comprises the fluorine-containing cyclic sulfate esters according to claim 1 and other additives.
5. A sodium ion battery electrolyte additive composition according to claim 4, characterized in that: The other additives are selected from fluorine-containing carbonates, including at least one of fluorine-containing cyclic carbonates and fluorine-containing linear carbonates. The amount of the other additives is 0.5-5% of the total mass of the non-aqueous electrolyte.
6. A sodium ion battery electrolyte additive composition according to claim 5, characterized in that: The other additives are selected from at least one of fluoroethylene carbonate (FEC), difluoroethylene carbonate (DFEC), trifluoromethylethylene carbonate (TFPC), 2,2,2-trifluoroethoxymethylethylene carbonate, hexafluoroisopropoxymethylethylene carbonate, 2,2,3,3,3-pentafluoropropoxymethylethylene carbonate, bis(trifluoromethyl)carbonate (DTFMC), bis(pentafluoroethyl)carbonate, bis(2,2,2-trifluoroethyl)carbonate, bis(2,2,3,3-tetrafluoropropyl)carbonate, methyl-2,2,2-trifluoroethylcarbonate (FEMC), ethyl-2,2,2-trifluoroethylcarbonate, (2,2,3,3,3-pentafluoropropyl)-methylcarbonate (PFPMC), and bis(fluoromethyl)carbonate.
7. A sodium ion battery electrolyte, comprising an electrolyte, a non-aqueous solvent and an additive, characterized in that: The additive comprises any one of claims 1 to 6 and a combination thereof.
8. A sodium ion battery non-aqueous electrolyte according to claim 7, characterized in that: The sodium salt electrolyte is at least one of sodium hexafluorophosphate, sodium difluorophosphate, sodium bis(oxalatoborate), sodium difluorooxalatoborate, sodium bis(fluorosulfonyl imide), sodium bis(trifluoromethylsulfonyl imide), sodium trifluoromethylsulfonate, sodium perchlorate, and sodium tetrafluoroborate. The molar concentration of the sodium salt electrolyte in the non-aqueous electrolyte is 0.8 to 1.5 mol / L.
9. The non-aqueous electrolyte for sodium ion batteries according to claim 7, characterized in that: The non-aqueous organic solvent is at least one of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, dipropyl carbonate, ethylene carbonate, methyl propyl carbonate, methyl butyl carbonate, propylene carbonate, γ-butyrolactone, methyl acetate, ethyl acetate, propyl acetate, butyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,2-dimethoxypropane, 2,2-dimethoxypropane, ethylene glycol dimethyl ether, tetrahydrofuran, and 2-methyltetrahydrofuran.
10. A sodium ion battery, characterized in that: The invention comprises a positive electrode material, a negative electrode material and the non-aqueous electrolyte according to any one of claims 7 to 9.
11. The sodium ion battery according to claim 10, characterized in that: The positive electrode material is selected from at least one of polyanion positive electrode materials, layered oxide positive electrode materials, and Prussian blue (Prussian white) positive electrode materials; the negative electrode material includes but is not limited to at least one of soft carbon, hard carbon, sodium titanate, and a metal that can form an alloy with sodium.
Citation Information
Cited By
Sodium ion battery suitable for backup power supply
CN120319874A
Electrolyte for sodium-ion battery as well as preparation method and application of electrolyte
CN120545471A
Sodium-ion battery with wide temperature range and long service life as well as preparation method and application of sodium-ion battery
CN120878944A
Secondary battery and electronic device
CN121394516A
Secondary battery and electronic device
CN121394516B
